Investigation on Tin based oxides as potential anode material for Li and Na ion batteries - Wang, Paul Luyuan (2017)
The heart of battery technology lies primarily in the electrode material, which is fundamental to how much charge can be stored and how long the battery can be cycled. Tin dioxide (SnO2) has received tremendous attention as an anode material in both Li-ion (LIB) and Na-ion (NIB) batteries, owing to benefits such as high specific capacity and rate capability. However, large volume expansion accompanying charging/discharging process results in poor cycability that hinders the utilization of SnO2 in commercial batteries. To this end, engineering solutions to surmount the limitations facing SnO2 as an anode in LIB/NIB will be presented in this thesis. The initial part of the thesis focuses on producing SnO2 and rGO (reduced graphene oxide)/SnO2 through laser pyrolysis and its application as an anode. The following segment studies the effect of nitrogen doping, where it was found to have a positive effect on SnO2 in LIB, but a detrimental effect in NIB. The final part of the thesis investigates the effect of matrix engineering through the production of a ZnSnO3 compound. Finally, the obtained results will be compared and to understand the implications that they may possess.